Evaluation of LoRa Deployment Through Site Survey on Irregular Terrain Model - Kramm, Humberto; Feldman, Max; Lima, Rafael; Viana, Lude; Müller, Ivan; Ferreira, Sandro Binsfeld (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2023: Anais do XIII Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2023)
The proper deployment of LoRa networks presents practical challenges due to the lack of an appropriate model to estimate its operability. To accelerate the process of area mapping in projects using this technology, this work compares simulation results using the Longley-Rice irregular terrain model with the results obtained from measurements performed in a highly irregular terrain. Using a properly configured simulation tool, a site survey is performed to determine the results for both line-of-sight and non-line-of-sight radio links. The testing environment is carefully chosen to ensure the reliability of the experiments. Based on this, it is possible to conclude that evaluating a coverage area for LoRa radio links by means of software tools in a flat ground presents satisfactory results, but lacks a more appropriate channel model for a rough terrain. The results show that the use of this technology in mountainous regions can achieve greater coverage in practice than that found in simulation software, suggesting that the software chosen for simulation underestimates the link capacity of a LoRa network.